Assessment of left ventricular impairment by calculating left ventricular impairment index using doppler echocardiography in chronic heart failure patients: Ultrazvočna ocena okvare levega prekata z doplersko ehokardiografijo in izračunom indeksa okvare levega prekata (iLVI) pri bolnikih s kroničnim srčnim popuščanjem - Krajnc, Igor; Sinkovič, Andreja (Acta Medico-Biotechnica, 2021)
Purpose: In order to assess global left ventricular impairment in chronic heart failure (HF) patients, it is necessary to consider both functional and structural changes of the left ventricle (LV), in particular, stroke volume (SV) and left ventricular end-diastolic diameter (LVEDD). Based on SV as a marker of LV function, LVEDD as a simple indicator of structural LV changes, and height of an individual patient (H), the left ventricular impairment index (iLVI) can be calculated. The purpose of this study was to assess the diagnostic value of iLVI in chronic HF patients.Methods: This prospective study included a total of 50 chronic HF patients and 50 healthy individuals, whounderwent standard two-dimensional echocardiography. The iLVI was calculated according to the formula: iLVI = SV x H / LVEDD2 (mL/cm). Results:The iLVI accurately separated healthy subjects from patients (AUC = 0.989), with the highest sensitivity and specificity for proper identification of HF (96.0% each),in comparison with ejection fraction (EF), stroke volume index (SVI), and SV/H. The iLVI effect was strong (Cohen’s d=3.2), exceeding that of EF, SVI, and SV/H.Conclusion: The study concluded that the iLVI, which can be readily calculated, represents an excellent clinical marker for global functional and/or structural LV impairment in chronic HF patients.
Keywords: echocardiography; left ventricular impairment; stroke volume; index; left ventricular end-diastolic diameter